Lead hafnate-based anti-ferroelectric ceramic with low phase transition electric field at high temperature and preparation method and application of lead hafnate-based anti-ferroelectric ceramic

Through the chemical composition and preparation process of modified lead hafnate-based ceramics, lead hafnate-based antiferroelectric ceramics with low phase transition electric fields were prepared, which solved the problems of poor energy storage performance and excessive phase transition electric fields in high temperature environments. , achieving improvements in energy storage performance and enhanced system safety at high temperatures.

CN119390442APending Publication Date: 2025-02-07TONGJI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411421712.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing lead hafnate-based ceramic materials have poor energy storage performance in high temperature environments and are too high in phase transition electric field, which has inherent risks at high voltages.

Method used

Through the chemical composition and preparation process of modified lead hafnate-based ceramics, the chemical composition of (Pb0.97La0.02)(HfxSn0.9-xTi0.1)O3 was prepared by casting method combined with isostatic pressure technology to obtain Lead hafnate based antiferroelectric ceramic with low phase transition electric field.

Benefits of technology

At high temperatures, the material exhibits antiferroelectric properties, the residual polarization is almost zero, the phase transition electric field is significantly reduced, and it can reach 3.2~3.8kV/mm, improving the energy storage performance and the safety and reliability of the system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390442A_ABST
    Figure CN119390442A_ABST
Patent Text Reader

Abstract

The invention relates to a lead hafnate-based anti-ferroelectric ceramic with a low phase transition electric field at a high temperature, and a preparation method and application of the lead hafnate-based anti-ferroelectric ceramic. The chemical composition of the lead hafnate-based ceramic material is (Pb < 0.97 > La < 0.02 >) (Hf < x > Sn < 0.9-x > Ti < 0.1 >) O < 3 >, wherein x is greater than or equal to 0.85 and less than or equal to 0.9. The material shows a ferroelectric hysteresis loop with ferroelectric characteristics and relatively large remanent polarization at room temperature, and shows double ferroelectric hysteresis loops at high temperature and shows antiferroelectric characteristics with a low phase transition electric field, the remanent polarization is almost zero, and the material is suitable for high-temperature energy storage scenes. Specifically, the anti-ferroelectric ceramic material can show the releasable energy density of 3.0-3.4 J / cm < 3 > under the high temperature of 120 DEG C and the low phase transition electric field of 3.2-3.8 kV / mm, the energy storage efficiency can reach 71.2-75.6%, the energy storage potential of the anti-ferroelectric ceramic material in the high-temperature environment is shown, and powerful support is provided for further research and development of high-temperature dielectric medium energy storage materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dielectric energy storage ceramics, and in particular to a lead hafniumate-based antiferroelectric ceramic with a low phase transition electric field at high temperature, and a preparation method and application thereof. Background Art

[0002] With the development of modern electronic devices and energy systems, the demand for high-performance energy storage materials continues to increase. Dielectric energy storage ceramics have broad application prospects in power electronics, energy storage devices, and pulse capacitors due to their high power density and rapid charging and discharging capabilities. Traditional dielectric energy storage materials often exhibit problems such as poor energy storage density in high-temperature environments, making it difficult to meet the needs of actual applications. For example, the common barium titanate (BaTiO3) material will experience a decrease in dielectric constant and an increase in loss at high temperatures, which makes it show obvious limitations in high-temperature energy storage applications. The releasable energy storage density (W rec ) can be calculated through the hysteresis loop, and the formula is: Among them, E represents the electric field strength, P represents the polarization strength, and P r and P max Represents the remnant polarization and the saturation polarization.

[0003] As a new type of dielectric energy storage material, lead hafnate-based ceramics have attracted much attention due to their excellent energy storage performance. However, existing lead hafnate-based ceramic materials still face some challenges in high-temperature environments, such as unsatisfactory energy storage performance. At the same time, if the phase transition electric field of the material is too high at high temperature, it will lead to inherent risks under high voltage and require expensive insulation technology. Studies have shown that by modifying the chemical composition and preparation process of lead hafnate-based ceramics, its energy storage performance at high temperature can be significantly improved and its phase transition electric field can be reduced.

[0004] Therefore, there is an urgent need for an antiferroelectric material that can be used in pulse power systems at high temperatures and low external electric fields. Summary of the invention

[0005] The purpose of the present invention is to provide a lead hafnate-based antiferroelectric ceramic with a low phase transition electric field at high temperature and a preparation method and application thereof, so as to solve the problems that the existing lead hafnate-based ceramic materials have unsatisfactory energy storage performance and excessively high phase transition electric field in a high temperature environment.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] The present invention provides a lead hafniumate-based antiferroelectric ceramic with a low phase transition electric field at high temperature. The chemical composition of the lead hafniumate-based antiferroelectric ceramic is (Pb 0.97 La 0.02 )(Hf x Sn0.9-x Ti 0.1 )O3, where 0.85≤x≤0.9.

[0008] Preferably, the chemical composition of the lead hafnium oxide-based antiferroelectric ceramic is (Pb 0.97 La 0.02 )(Hf 0.85 Sn 0.05 Ti 0.1 )O3, x=0.85.

[0009] Preferably, the lead hafniumate-based antiferroelectric ceramic exhibits antiferroelectric properties and has a double hysteresis loop under test conditions of 100 to 120° C. and 10 Hz and an applied electric field of 10 to 40 kV / mm.

[0010] Preferably, the lead hafnate-based antiferroelectric ceramic has a low phase transition electric field of 3.2 to 3.8 kV / mm under the test conditions of 100 to 120° C. and 10 Hz and an applied electric field of 10 to 40 kV / mm, and exhibits a low phase transition electric field of 3.0 to 3.4 J / cm 3 The releasable energy density, residual polarization intensity P r 0.08~0.3μC / cm 2 , the maximum saturation polarization intensity P m 50.2~52.7μC / cm 2 .

[0011] Further preferably, when the chemical composition of the lead hafnium oxide-based antiferroelectric ceramic is (Pb 0.97 La 0.02 )(Hf 0.85 Sn 0.05 Ti 0.1 )O3, the lead hafnate-based antiferroelectric ceramic exhibits antiferroelectric properties under the test conditions of 120°C and 10 Hz and an applied electric field of 10 to 40 kV / mm, has a low phase transition electric field of 3.5 kV / mm, and exhibits a high conductivity of 3.4 J / cm 3 of releasable energy density.

[0012] In a second aspect, the present invention provides a method for preparing the above-mentioned lead hafniumate-based antiferroelectric ceramic with a low phase transition electric field at high temperature, comprising the following steps:

[0013] S1, press (Pb 0.97 La 0.02 )(Hf 0.85 Sn 0.05 Ti 0.1)O3, weighing PbO, La2O3, HfO2, SnO2 and TiO2 as raw materials, and sequentially performing a first ball milling, a pre-sintering and a second ball milling treatment to prepare a lead hafnium oxide-based antiferroelectric ceramic powder;

[0014] S2, mixing the lead hafnium oxide-based antiferroelectric ceramic powder prepared in step S1 with a solvent, a dispersant, a binder and a plasticizer to obtain a lead hafnium oxide-based antiferroelectric ceramic slurry;

[0015] S3, performing tape casting treatment on the lead hafnium oxide-based antiferroelectric current casting slurry obtained in step S2 to obtain a lead hafnium oxide-based antiferroelectric thick film;

[0016] S4, hot pressing and isostatic pressing the lead hafnium oxide-based antiferroelectric thick film obtained in step S3 to obtain a ceramic green body;

[0017] S5, performing debinding and sintering treatments on the ceramic green body obtained in step S4 to prepare a lead hafnium oxide-based antiferroelectric ceramic material.

[0018] Preferably, in step S1, when weighing the PbO, the mass of the PbO exceeds (Pb 0.97 La 0.02 )(Hf 0.85 Sn 0.05 Ti 0.1 )O3 is 1 to 2 wt% of the mass calculated based on the molar ratio of each element in order to compensate for the volatilization of lead at high temperatures.

[0019] Preferably, in step S1, the dispersant for the primary ball milling and the secondary ball milling includes water or anhydrous ethanol, the medium used for ball milling is zirconia balls, the ball milling time is 12 to 18 hours, and the ball milling speed is 360 to 450 rpm.

[0020] Preferably, the mass ratio of the mixed powder of raw materials such as PbO, La2O3, HfO2, SnO2 and TiO2, the dispersant and the zirconia balls is (1.3-1.8):(1.3-1.8):(2.0-2.8).

[0021] Preferably, in step S1, the pre-sintering temperature is 880-910°C, the pre-sintering holding time is 2-3h, and the heating rate is 2-3°C / min.

[0022] Preferably, in step S2, the solvent comprises a mixture of anhydrous ethanol and butanone; the dispersant comprises tributyl phosphate; the binder comprises polyvinyl butyral; and the plasticizer comprises a mixture of polyethylene glycol and benzyl-n-butyl-phthalate.

[0023] Further preferably, in step S2, the amount of anhydrous ethanol added is 50-55% of the mass of the ceramic powder; the amount of butanone added is the same as the mass of the ceramic powder; the amount of tributyl phosphate added is 3-4% of the mass of the ceramic powder; the amount of polyvinyl butyral added is 9.5-10.5% of the mass of the ceramic powder; the amount of polyethylene glycol added is 3-4% of the mass of the ceramic powder; and the amount of benzyl-n-butyl-phthalate added is 3-4% of the mass of the ceramic powder.

[0024] Preferably, in step S3, the casting rate is 20-30 cm / min, and the thickness of the lead hafnium oxide-based antiferroelectric thick film is 15-25 μm.

[0025] Preferably, in step S4, the hot pressing temperature is 45-60° C., the pressure is 120-150 MPa, and the hot pressing time is 8-10 min; the isostatic pressing temperature is room temperature, the pressure is 180-200 MPa, and the holding time is 10-15 min.

[0026] Preferably, in step S5, the debinding process includes heating the temperature to 550-600°C at a heating rate of 0.5-1°C / min and keeping the temperature for 10-15 hours; the sintering process includes heating the temperature to 1250-1300°C at a heating rate of 1-2°C / min and keeping the temperature for 2-3 hours.

[0027] In a third aspect, the present invention also provides an application of the above-mentioned lead hafniumate-based antiferroelectric ceramic with a low phase transition electric field at high temperature in the field of pulse power and high-temperature energy storage.

[0028] Preferably, the application includes application in the preparation of high-temperature power electronic equipment, high-temperature energy storage devices and high-temperature pulse capacitors.

[0029] The present invention provides a lead hafnate-based antiferroelectric ceramic with a low phase transition electric field at high temperature, and a preparation method and application thereof. By modifying the chemical composition and optimizing the preparation process, a lead hafnate-based antiferroelectric ceramic is obtained which exhibits antiferroelectric properties in a high temperature environment, has almost zero residual polarization and has a low phase transition electric field.

[0030] The present invention provides a promising antiferroelectric material for pulse power applications at high temperatures and low external electric fields. The present invention optimizes the chemical composition of lead hafnate-based ceramics by introducing an appropriate amount of element doping, and prepares the antiferroelectric ceramic material by using a tape casting method combined with an isostatic pressing process. The material exhibits a hysteresis loop with ferroelectric characteristics at room temperature and a large residual polarization, while at high temperatures it exhibits a double hysteresis loop, showing antiferroelectric properties with a low phase transition electric field and almost zero residual polarization. The low phase transition electric field can effectively reduce the operating voltage requirements of high-temperature energy storage systems, reduce the complexity and cost of insulation technology, and improve the safety and reliability of the system. The material of the present invention has broad application prospects in the field of high-temperature energy storage.

[0031] The antiferroelectric material provided by the present invention is located near the phase boundary, exhibits ferroelectric characteristics at room temperature, gradually exhibits antiferroelectric characteristics as the temperature rises, and has a lower phase transition electric field. Since the material crystal structure near the phase boundary is in a transition state between a ferroelectric phase and an antiferroelectric phase, the structure is unstable and is very sensitive to external stimuli (such as temperature or electric field). As the temperature rises, thermal excitation inside the material will increase the disorder of the electric dipole, weaken the orderly arrangement of the ferroelectric domain, and cause the ferroelectricity to gradually weaken. When the temperature is high enough, the ferroelectric phase gradually changes to the antiferroelectric phase, and the material exhibits antiferroelectric characteristics. This transition is usually accompanied by a lower phase transition electric field, because thermal excitation at high temperature can reduce the energy barrier of the antiferroelectric phase, so that a smaller external electric field can induce the transition of the antiferroelectric to the ferroelectric phase.

[0032] Compared with the prior art, the antiferroelectric material component of the present invention is located near the phase boundary, exhibiting ferroelectric properties at room temperature, but exhibiting an extremely low antiferroelectric-ferroelectric phase transition electric field (3.2-3.8 kV / mm) at high temperatures. When the phase transition electric field is reduced by about 3 times, the material can still exhibit a high releasable energy storage density (3.0-3.4 J / cm 3 ).

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The present invention obtains a lead hafnium oxide-based antiferroelectric ceramic material by modifying the chemical composition of the ceramic, the chemical formula of which is (Pb 0.97 La 0.02 )(Hf x Sn 0.9-x Ti 0.1)O3, where 0.85≤x≤0.9. Conventional dielectric energy storage materials exhibit poor energy storage density in high temperature environments. In contrast, the material of the present invention exhibits good energy storage performance at high temperatures. Under high temperature conditions of 100-120°C, the material exhibits a double hysteresis loop, exhibits antiferroelectric properties, has almost zero residual polarization, and can release energy density up to 3.4 J / cm 3 .

[0035] (2) The lead hafnium oxide-based antiferroelectric ceramic material of the present invention has a low phase transition electric field of 3.2 to 3.8 kV / mm at high temperature, which significantly reduces the operating voltage requirements. This feature not only reduces the inherent risks under high voltage, but also reduces the requirements for insulation technology, thereby reducing the complexity and cost of the energy storage system.

[0036] (3) The present invention adopts a tape casting method combined with an isostatic pressing process to prepare ceramic materials, which fully utilizes the advantages of the two processes and significantly improves the uniformity and density of the ceramic materials, thereby improving the dielectric properties and energy storage performance of the materials.

[0037] (4) The lead hafnium oxide-based antiferroelectric ceramic material prepared by the present invention is suitable for various high-temperature energy storage scenarios, showing broad application prospects in high-temperature power electronic equipment, high-temperature energy storage devices and high-temperature pulse capacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The XRD spectrum of the lead hafniumate-based antiferroelectric ceramic prepared in Example 1 of the present invention;

[0039] Figure 2 is a hysteresis loop diagram of the lead hafniumate-based antiferroelectric ceramic prepared in Example 1 of the present invention at room temperature;

[0040] Figure 3 1 is a hysteresis loop diagram of the lead hafnium oxide-based antiferroelectric ceramic prepared in Example 1 of the present invention at a high temperature of 120° C.;

[0041] Figure 4 hysteresis loop diagrams of the lead hafnium oxide-based antiferroelectric ceramic prepared in Example 1 of the present invention at a high temperature of 120° C. under different applied electric fields;

[0042] Figure 5 The current loop diagram of the lead hafnium oxide-based antiferroelectric ceramic prepared in Example 1 of the present invention at a high temperature of 120° C. under different applied electric fields;

[0043] Figure 6 The lead hafnium oxide-based antiferroelectric ceramic prepared in Example 1 of the present invention can release energy density (W rec ) changes with the applied electric field. DETAILED DESCRIPTION

[0044] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0045] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0046] The present invention provides a lead hafniumate-based antiferroelectric ceramic with a low phase transition electric field at high temperature. The chemical composition of the lead hafniumate-based antiferroelectric ceramic is (Pb 0.97 La 0.02 )(Hf x Sn 0.9-x Ti 0.1 )O3, wherein 0.85≤x≤0.9, the lead hafnate-based antiferroelectric ceramic exhibits antiferroelectric properties under the test conditions of 120°C and 10 Hz and an applied electric field of 10 to 40 kV / mm, has a double hysteresis loop, has a low phase transition electric field of 3.2 to 3.8 kV / mm, and exhibits a high conductivity of 3.0 to 3.4 J / cm 3 The releasable energy density, residual polarization intensity P r 0.08~0.3μC / cm 2 , the maximum saturation polarization intensity P m 50.2~52.7μC / cm 2 .

[0047] The lead hafnium oxide-based antiferroelectric ceramic is prepared by the following process:

[0048] S1, weigh the corresponding mass of PbO, La2O3, HfO2, SnO2 and TiO2 powders according to the molar ratio, wherein PbO should be in excess of 1-2wt% to compensate for the volatilization of lead at high temperature. The above powders are ball-milled once, the dispersant in the ball-milling process is water or anhydrous ethanol, the ball-milling medium is zirconia balls or agate balls, the ball-milling time is 12-18h, and the ball-milling speed is 360-450rpm. The powder after the first ball-milling is pre-sintered, the pre-sintering temperature is 880-910℃, the insulation time is 2-3h, and the heating rate is 2-3℃ / min. The pre-sintered powder is ball-milled for the second time, and the process parameters of the second ball-milling are the same as those of the first ball-milling. After the second ball-milling, the final lead hafnium oxide-based antiferroelectric ceramic powder can be obtained;

[0049] S2, the lead hafniumate-based antiferroelectric ceramic powder obtained in step S1 is mixed evenly with a solvent (anhydrous ethanol and butanone), a dispersant (tributyl phosphate), a binder (polyvinyl butyral) and a plasticizer (polyethylene glycol and benzyl-n-butyl-phthalate) to prepare the required casting slurry. The specific formula is as follows: the amount of anhydrous ethanol added is 50-55% of the mass of the raw material powder; the amount of butanone added is the same as the mass of the raw material powder; the amount of tributyl phosphate added is 3-4% of the mass of the raw material powder; the amount of polyvinyl butyral added is 9.5-10.5% of the mass of the raw material powder; the amount of polyethylene glycol added is 3-4% of the mass of the raw material powder; the amount of benzyl-n-butyl-phthalate added is 3-4% of the mass of the raw material powder;

[0050] S3, the slurry obtained in step S2 is subjected to tape casting to prepare a lead hafnate-based antiferroelectric ceramic thick film. The thick film is then subjected to hot pressing treatment, with the temperature set to 45-60°C, the pressure set to 120-150 MPa, and the hot pressing time being 8-10 minutes, followed by isostatic pressing treatment, with the pressure set to 180-200 MPa, and the holding time being 10-15 minutes, thereby obtaining a lead hafnate-based antiferroelectric ceramic green body;

[0051] S4, the ceramic green body obtained in step S3 is subjected to binder removal treatment at 550-600°C, kept at this temperature for 10-15 hours, and the heating rate is controlled at 0.5-1°C / min. Then, it is subjected to sintering treatment at 1250-1300°C, kept at this temperature for 2-3 hours, and the heating rate is controlled at 1-2°C / min. After the above steps, the lead hafnium oxide-based antiferroelectric ceramic material is finally obtained.

[0052] The present invention is further described below through specific examples.

[0053] Example 1

[0054] This embodiment provides a lead hafniumate-based antiferroelectric ceramic with a low phase transition electric field at high temperature, and its chemical composition is: (Pb 0.97 La 0.02 )(Hf 0.85 Sn 0.05 Ti 0.1 )O3, the specific preparation method is as follows:

[0055] S1. First, weigh the corresponding masses of PbO, La2O3, HfO2, SnO2 and TiO2 oxide powders according to the molar ratio. Among them, PbO is in excess of 2wt%. The above raw material powders are ball-milled once with the dispersant anhydrous ethanol. The ball milling medium is zirconia balls. The ball milling time is 18 hours and the ball milling speed is set to 450rpm. Then the powder after the first ball milling is pre-sintered. The pre-sintering temperature is set to 910°C, the insulation time is 3 hours, and the heating rate is controlled at 3°C / min. The pre-sintered powder is then ball-milled for a second time with the dispersant anhydrous ethanol. The ball milling medium is still zirconia balls, and the ball milling time lasts for 18 hours. After the second ball milling, the final lead hafnium oxide-based antiferroelectric ceramic powder is obtained;

[0056] S2. Fully mix the ceramic powder obtained in step S1 with solvent (anhydrous ethanol and butanone), dispersant (tributyl phosphate), binder (polyvinyl butyral) and plasticizer (polyethylene glycol and benzyl-n-butyl-phthalate) to prepare hafnium oxide-based antiferroelectric current rolling slurry. Among them, the amount of anhydrous ethanol added is 55% of the mass of the raw material powder; the amount of butanone added is the same as the mass of the raw material powder; the amount of tributyl phosphate added is 4% of the mass of the raw material powder; the amount of polyvinyl butyral added is 10.5% of the mass of the raw material powder; the amount of polyethylene glycol added is 4% of the mass of the raw material powder; the amount of benzyl-n-butyl-phthalate added is 4% of the mass of the raw material powder;

[0057] S3, the slurry prepared in step S2 is subjected to tape casting to obtain a lead hafnium oxide-based antiferroelectric ceramic thick film. The thick film is then subjected to hot pressing, with the temperature set to 60°C, the pressure set to 150 MPa, and the hot pressing time set to 10 min. It is then subjected to isostatic pressing, with the pressure set to 200 MPa and the holding time set to 15 min, to obtain a lead hafnium oxide-based antiferroelectric ceramic green body;

[0058] S4, the ceramic green body obtained in step S3 is first subjected to binder removal at 600°C, the holding time is 15 hours, and the heating rate is controlled at 1°C / min. Then, it is sintered at 1300°C, the holding time is 3 hours, and the heating rate is controlled at 2°C / min. Through the above steps, the lead hafnium oxide-based antiferroelectric ceramic material is finally obtained.

[0059] The lead hafnium oxide-based antiferroelectric ceramic prepared in the embodiment of the present invention was subjected to X-ray diffraction analysis, and the following results were obtained: Figure 1 As shown in the XRD pattern, it can be seen that all diffraction peaks correspond to a single perovskite phase without any impurity phase.

[0060] The hysteresis loop test of the lead hafnate-based antiferroelectric ceramic prepared in the embodiment of the present invention was performed at a test frequency of 10 Hz using a Premier II ferroelectric analyzer from Radiant Corporation of the United States. Figure 2The hysteresis loop diagram of the ceramic at room temperature (25°C) is shown, showing a hysteresis loop with ferroelectric characteristics and a large remanent polarization. Figure 3 The hysteresis loop diagram of the ceramic at a high temperature of 120°C is shown, showing a double hysteresis loop, exhibiting antiferroelectric properties, and the residual polarization is almost zero, which greatly improves the releasable energy density, indicating that the material is suitable for high-temperature environments.

[0061] Figure 4 The hysteresis loop diagram of the lead hafnate-based antiferroelectric ceramic prepared in the embodiment of the present invention under different applied electric fields at a high temperature of 120°C is shown. It can be seen that under high temperature environment, the ceramic prepared in the embodiment of the present invention exhibits double hysteresis loops under different applied electric fields, and as the applied electric field increases, the residual polarization remains almost zero, and the saturation polarization shows an increasing trend. Under an applied electric field of 40 kV / mm, the saturation polarization reaches a maximum value of 52.7 μC / cm 2 This indicates that the lead hafnium oxide-based antiferroelectric ceramics prepared in the embodiments of the present invention have broad application prospects in high-temperature energy storage devices.

[0062] Figure 5 The current loop diagram of the lead hafnate-based antiferroelectric ceramic prepared by the embodiment of the present invention under different applied electric fields at a high temperature of 120°C is shown. It can be seen that under high temperature environment, the ceramic prepared by the embodiment of the present invention exhibits a low phase transition electric field of 3.5kV / mm under different external electric fields. The low phase transition electric field is conducive to reducing the operating voltage of the high-temperature energy storage system, thereby reducing the inherent risks under high voltage, and also reducing the cost and requirements for insulation technology.

[0063] Figure 6 It shows that the lead hafnium oxide-based antiferroelectric ceramics prepared in the embodiment of the present invention can release energy density (W) at a high temperature of 120°C. rec ) changes with the applied electric field. It can be seen that under high temperature environment, with the increase of the applied electric field, the releasable energy density shows an increasing trend, and finally 3.4J / cm 3 The releasable energy density and energy storage efficiency of 75.5% indicate that the lead hafnium oxide-based antiferroelectric ceramics prepared in the embodiments of the present invention exhibit excellent application prospects in high temperature environments.

[0064] Example 2

[0065] This embodiment provides a lead hafniumate-based antiferroelectric ceramic with a low phase transition electric field at high temperature, and its chemical composition is: (Pb 0.97 La 0.02 )(Hf 0.85 Sn 0.05 Ti 0.1 )O3, the specific preparation method is as follows:

[0066] S1. First, weigh the corresponding masses of PbO, La2O3, HfO2, SnO2 and TiO2 oxide powders according to the molar ratio. Among them, the excess of PbO is 1.5wt%. The above raw material powders are ball-milled together with the dispersant anhydrous ethanol. The ball milling medium is zirconia balls. The ball milling time is 15h and the ball milling speed is set to 400rpm. Then the powder after the first ball milling is pre-sintered. The pre-sintering temperature is set to 900℃, the insulation time is 2.5h, and the heating rate is controlled at 2.5℃ / min. The pre-sintered powder is then ball-milled for a second time with the dispersant anhydrous ethanol. The ball milling medium is still zirconia balls, and the ball milling time lasts for 15h. After the second ball milling, the final lead hafnium oxide-based antiferroelectric ceramic powder is obtained;

[0067] S2. Fully mix the ceramic powder obtained in step S1 with solvent (anhydrous ethanol and butanone), dispersant (tributyl phosphate), binder (polyvinyl butyral) and plasticizer (polyethylene glycol and benzyl-n-butyl-phthalate) to prepare hafnium oxide-based antiferroelectric current rolling slurry. Among them, the amount of anhydrous ethanol added is 53% of the mass of the raw material powder; the amount of butanone added is the same as the mass of the raw material powder; the amount of tributyl phosphate added is 3.5% of the mass of the raw material powder; the amount of polyvinyl butyral added is 10% of the mass of the raw material powder; the amount of polyethylene glycol added is 3.5% of the mass of the raw material powder; the amount of benzyl-n-butyl-phthalate added is 3.5% of the mass of the raw material powder;

[0068] S3, the slurry prepared in step S2 is subjected to tape casting to obtain a lead hafnium oxide-based antiferroelectric ceramic thick film. The thick film is then subjected to hot pressing, with the temperature set to 55°C, the pressure set to 130 MPa, and the holding time being 9 minutes. It is then subjected to isostatic pressing, with the pressure set to 190 MPa and the holding time being 12 minutes, to obtain a lead hafnium oxide-based antiferroelectric ceramic green body;

[0069] S4, the ceramic green body obtained in step S3 is first subjected to binder removal at 580°C, the holding time is 13h, and the heating rate is controlled at 0.8°C / min. Then, it is sintered at 1280°C, the holding time is 2.5h, and the heating rate is controlled at 1.5°C / min. Through the above steps, the lead hafnium oxide-based antiferroelectric ceramic material is finally obtained.

[0070] The ceramic prepared in this example exhibits a hysteresis loop with ferroelectric characteristics at room temperature, and the residual polarization is large. At a high temperature of 120°C, it exhibits a double hysteresis loop, showing antiferroelectric characteristics, and the residual polarization is almost zero. At a high temperature of 120°C, with the increase of the applied electric field, the saturation polarization shows an increasing trend, reaching a maximum value of 51μC / cm at an applied electric field of 38kV / mm. 2Under different external electric fields, the ceramics prepared in the embodiments of the present invention all showed a low phase transition electric field of 3.7 kV / mm. Under a high temperature environment of 120°C, with the increase of the external electric field, the releasable energy density showed an increasing trend. Finally, under a low phase transition electric field of 3.7 kV / mm, 3.4 J / cm 3 The releasable energy density and energy storage efficiency of 74.8% are achieved.

[0071] Example 3

[0072] This embodiment provides a lead hafniumate-based antiferroelectric ceramic with a low phase transition electric field at high temperature, and its chemical composition is: (Pb 0.97 La 0.02 )(Hf 0.85 Sn 0.05 Ti 0.1 )O3, the specific preparation method is as follows:

[0073] S1. First, weigh the corresponding masses of PbO, La2O3, HfO2, SnO2 and TiO2 oxide powders according to the molar ratio. Among them, PbO has an excess of 1wt%. The above raw material powders are ball-milled together with dispersant water. The ball milling medium is zirconia balls. The ball milling time is 12h and the ball milling speed is set to 360rpm. Then the powder after the first ball milling is pre-sintered. The pre-sintering temperature is set to 880℃, the insulation time is 2h, and the heating rate is controlled at 2℃ / min. The pre-sintered powder is then ball-milled for a second time with dispersant water. The ball milling medium is still zirconia balls, and the ball milling time lasts for 12h. After the second ball milling, the final lead hafnium oxide-based antiferroelectric ceramic powder is obtained;

[0074] S2. Fully mix the ceramic powder obtained in step S1 with solvent (anhydrous ethanol and butanone), dispersant (tributyl phosphate), binder (polyvinyl butyral) and plasticizer (polyethylene glycol and benzyl-n-butyl-phthalate) to prepare hafnium oxide-based antiferroelectric current rolling slurry. Among them, the amount of anhydrous ethanol added is 50% of the mass of the raw material powder; the amount of butanone added is the same as the mass of the raw material powder; the amount of tributyl phosphate added is 3% of the mass of the raw material powder; the amount of polyvinyl butyral added is 9.5% of the mass of the raw material powder; the amount of polyethylene glycol added is 3% of the mass of the raw material powder; the amount of benzyl-n-butyl-phthalate added is 3% of the mass of the raw material powder;

[0075] S3, the slurry prepared in step S2 is subjected to tape casting to obtain a lead hafnium oxide-based antiferroelectric ceramic thick film. The thick film is then subjected to hot pressing, with the temperature set to 45°C, the pressure set to 120 MPa, and the holding time being 8 minutes. It is then subjected to isostatic pressing, with the pressure set to 180 MPa and the holding time being 10 minutes, to obtain a lead hafnium oxide-based antiferroelectric ceramic green body;

[0076] S4, the ceramic green body obtained in step S3 is first subjected to binder removal at 550°C, the holding time is 10 hours, and the heating rate is controlled at 0.5°C / min. Then, it is sintered at 1250°C, the holding time is 2 hours, and the heating rate is controlled at 1°C / min. Through the above steps, the lead hafnium oxide-based antiferroelectric ceramic material is finally obtained.

[0077] The ceramic prepared in this example exhibits a hysteresis loop with ferroelectric characteristics at room temperature, and the residual polarization is large. At a high temperature of 120°C, it exhibits a double hysteresis loop, showing antiferroelectric characteristics, and the residual polarization is almost zero. At a high temperature of 120°C, with the increase of the applied electric field, the saturation polarization shows an increasing trend, reaching a maximum value of 50.2μC / cm at an applied electric field of 37kV / mm. 2 Under different external electric fields, the ceramics prepared in the embodiments of the present invention all showed a low phase transition electric field of 3.8 kV / mm. Under a high temperature environment of 120°C, with the increase of the external electric field, the releasable energy density showed an increasing trend. Finally, under a low phase transition electric field of 3.8 kV / mm, 3.3 J / cm 3 The releasable energy density and energy storage efficiency of 75.6% are achieved.

[0078] Example 4

[0079] This embodiment provides a lead hafniumate-based antiferroelectric ceramic with a low phase transition electric field at high temperature, and its chemical composition is: (Pb 0.97 La 0.02 )(Hf 0.9 Ti 0.1 )O3, the specific preparation method is as follows:

[0080] S1. First, weigh the corresponding masses of PbO, La2O3, HfO2, SnO2 and TiO2 oxide powders according to the molar ratio. Among them, the excess of PbO is 1.2wt%. The above raw material powders are ball-milled once with the dispersant anhydrous ethanol. The ball milling medium is zirconia balls. The ball milling time is 13h and the ball milling speed is set to 380rpm. Then the powder after the first ball milling is pre-sintered. The pre-sintering temperature is set to 890℃, the insulation time is 2.4h, and the heating rate is controlled at 2.3℃ / min. The pre-sintered powder is then ball-milled for a second time with the dispersant anhydrous ethanol. The ball milling medium is still zirconia balls, and the ball milling time lasts for 13h. After the second ball milling, the final lead hafnium oxide-based antiferroelectric ceramic powder is obtained;

[0081] S2. Fully mix the ceramic powder obtained in step S1 with solvent (anhydrous ethanol and butanone), dispersant (tributyl phosphate), binder (polyvinyl butyral) and plasticizer (polyethylene glycol and benzyl-n-butyl-phthalate) to prepare hafnium oxide-based antiferroelectric current rolling slurry. Among them, the amount of anhydrous ethanol added is 51% of the mass of the raw material powder; the amount of butanone added is the same as the mass of the raw material powder; the amount of tributyl phosphate added is 3.2% of the mass of the raw material powder; the amount of polyvinyl butyral added is 9.7% of the mass of the raw material powder; the amount of polyethylene glycol added is 3.2% of the mass of the raw material powder; the amount of benzyl-n-butyl-phthalate added is 3.2% of the mass of the raw material powder;

[0082] S3, the slurry prepared in step S2 is subjected to tape casting to obtain a lead hafnium oxide-based antiferroelectric ceramic thick film. The thick film is then subjected to hot pressing, with the temperature set to 50°C, the pressure set to 125 MPa, and the hot pressing time set to 8.5 min. It is then subjected to isostatic pressing, with the pressure set to 185 MPa and the holding time set to 11 min, to obtain a lead hafnium oxide-based antiferroelectric ceramic green body;

[0083] S4, the ceramic green body obtained in step S3 is first subjected to binder removal at 570°C, the holding time is 12h, and the heating rate is controlled at 0.6°C / min. Then, it is sintered at 1270°C, the holding time is 2.4h, and the heating rate is controlled at 1.2°C / min. Through the above steps, the lead hafnium oxide-based antiferroelectric ceramic material is finally obtained.

[0084] The ceramic prepared in this example exhibits a hysteresis loop with ferroelectric characteristics at room temperature, and the residual polarization is large. At a high temperature of 120°C, it exhibits a double hysteresis loop, showing antiferroelectric characteristics, and the residual polarization is almost zero. At a high temperature of 120°C, with the increase of the applied electric field, the saturation polarization shows an increasing trend, reaching a maximum value of 51.3μC / cm at an applied electric field of 39kV / mm. 2 Under different external electric fields, the ceramics prepared in the embodiments of the present invention all showed a low phase transition electric field of 3.2 kV / mm. Under a high temperature environment of 120°C, with the increase of the external electric field, the releasable energy density showed an increasing trend. Finally, under a low phase transition electric field of 3.2 kV / mm, 3.0 J / cm 3 The releasable energy density and energy storage efficiency of 71.2% are achieved.

[0085] Example 5

[0086] This embodiment provides a lead hafniumate-based antiferroelectric ceramic with a low phase transition electric field at high temperature, and its chemical composition is: (Pb 0.97 La 0.02 )(Hf 0.85 Sn 0.05 Ti0.1 )O3, the specific preparation method is as follows:

[0087] S1. First, weigh the corresponding masses of PbO, La2O3, HfO2, SnO2 and TiO2 oxide powders according to the molar ratio. Among them, the excess of PbO is 1.7wt%. The above raw material powders are ball-milled once with the dispersant anhydrous ethanol. The ball milling medium is zirconia balls. The ball milling time is 16h and the ball milling speed is set to 420rpm. Then the powder after the first ball milling is pre-sintered. The pre-sintering temperature is set to 905℃, the insulation time is 2.7h, and the heating rate is controlled at 2.8℃ / min. The pre-sintered powder is then ball-milled for a second time with the dispersant anhydrous ethanol. The ball milling medium is still zirconia balls, and the ball milling time lasts for 16h. After the second ball milling, the final lead hafnium oxide-based antiferroelectric ceramic powder is obtained;

[0088] S2. Fully mix the ceramic powder obtained in step S1 with solvent (anhydrous ethanol and butanone), dispersant (tributyl phosphate), binder (polyvinyl butyral) and plasticizer (polyethylene glycol and benzyl-n-butyl-phthalate) to prepare hafnium oxide-based antiferroelectric current rolling slurry. Among them, the amount of anhydrous ethanol added is 54% of the mass of the raw material powder; the amount of butanone added is the same as the mass of the raw material powder; the amount of tributyl phosphate added is 3.8% of the mass of the raw material powder; the amount of polyvinyl butyral added is 10.3% of the mass of the raw material powder; the amount of polyethylene glycol added is 3.6% of the mass of the raw material powder; the amount of benzyl-n-butyl-phthalate added is 3.6% of the mass of the raw material powder;

[0089] S3, the slurry prepared in step S2 is subjected to tape casting to obtain a lead hafnate-based antiferroelectric ceramic thick film. The thick film is then subjected to hot pressing, with the temperature set to 57°C, the pressure set to 140 MPa, and the hot pressing time set to 9.5 min. It is then subjected to isostatic pressing, with the pressure set to 195 MPa and the holding time set to 13 min, to obtain a lead hafnate-based antiferroelectric ceramic green body;

[0090] S4, the ceramic green body obtained in step S3 is first subjected to binder removal at 590°C, the holding time is 14h, and the heating rate is controlled at 0.9°C / min. Then, it is sintered at 1290°C, the holding time is 2.9h, and the heating rate is controlled at 1.8°C / min. Through the above steps, the lead hafnium oxide-based antiferroelectric ceramic material is finally obtained.

[0091] The ceramic prepared in this example exhibits a hysteresis loop with ferroelectric characteristics at room temperature, and the residual polarization is large. At a high temperature of 100°C, it exhibits a double hysteresis loop, showing antiferroelectric characteristics, and the residual polarization is almost zero. At a high temperature of 100°C, with the increase of the applied electric field, the saturation polarization shows an increasing trend, reaching a maximum value of 51.7μC / cm at an applied electric field of 40kV / mm. 2 Under different external electric fields, the ceramics prepared in the embodiments of the present invention all showed a low phase transition electric field of 3.2 kV / mm. Under a high temperature environment of 100°C, with the increase of the external electric field, the releasable energy density showed an increasing trend. Finally, under a low phase transition electric field of 3.2 kV / mm, 3.1 J / cm 3 The releasable energy density and energy storage efficiency of 75.2% are achieved.

[0092] Comparative Example 1

[0093] This comparative example provides a lead hafnium oxide-based antiferroelectric ceramic, the chemical composition of which is: (Pb 0.97 La 0.02 )(Hf 0.65 Sn 0.25 Ti 0.1 )O3, the specific preparation method is as follows:

[0094] S1. First, weigh the corresponding masses of PbO, La2O3, HfO2, SnO2 and TiO2 oxide powders according to the molar ratio. Among them, PbO has an excess of 1.6wt%. The above raw material powders are ball-milled together with dispersant water. The ball milling medium is zirconia balls. The ball milling time is 14h and the ball milling speed is set to 430rpm. Then the powder after the first ball milling is pre-sintered. The pre-sintering temperature is set to 895℃, the insulation time is 2.2h, and the heating rate is controlled at 2.4℃ / min. The pre-sintered powder is then ball-milled for a second time with dispersant water. The ball milling medium is still zirconia balls, and the ball milling time lasts for 14h. After the second ball milling, the final lead hafnium oxide-based antiferroelectric ceramic powder is obtained;

[0095] S2. Fully mix the ceramic powder obtained in step S1 with solvent (anhydrous ethanol and butanone), dispersant (tributyl phosphate), binder (polyvinyl butyral) and plasticizer (polyethylene glycol and benzyl-n-butyl-phthalate) to prepare hafnium oxide-based antiferroelectric current rolling slurry. Among them, the amount of anhydrous ethanol added is 52% of the mass of the raw material powder; the amount of butanone added is the same as the mass of the raw material powder; the amount of tributyl phosphate added is 3.6% of the mass of the raw material powder; the amount of polyvinyl butyral added is 10.1% of the mass of the raw material powder; the amount of polyethylene glycol added is 3.3% of the mass of the raw material powder; the amount of benzyl-n-butyl-phthalate added is 3.3% of the mass of the raw material powder;

[0096] S3, the slurry prepared in step S2 is subjected to tape casting to obtain a lead hafnium oxide-based antiferroelectric ceramic thick film. The thick film is then subjected to hot pressing, with the temperature set to 56°C, the pressure set to 145MPa, and the holding time being 8.2min. It is then subjected to isostatic pressing, with the pressure set to 192MPa and the holding time being 14min, to obtain a lead hafnium oxide-based antiferroelectric ceramic green body;

[0097] S4, the ceramic green body obtained in step S3 is first subjected to binder removal at 560°C, the holding time is 11 hours, and the heating rate is controlled at 0.7°C / min. Then, it is sintered at 1260°C, the holding time is 2.8 hours, and the heating rate is controlled at 1.3°C / min. Through the above steps, the lead hafnium oxide-based antiferroelectric ceramic material is finally obtained.

[0098] The ceramic prepared in this comparative example exhibits double hysteresis loops at room temperature, showing antiferroelectric properties, and the remanent polarization is close to zero. With the increase of the applied electric field, the saturation polarization shows an increasing trend, reaching a maximum value of 47.9μC / cm at an applied electric field of 21kV / mm. 2 The phase transition electric field of the ceramic at room temperature is 5kV / mm. As the temperature rises, the phase transition electric field gradually increases. At a high temperature of 120°C, the phase transition electric field reaches 5.7kV / mm. This makes it difficult to reduce the operating voltage of the material at high temperatures, increases the inherent risks in high-voltage operations, and also increases the cost and requirements for insulation technology.

[0099] The ceramic material (Pb 0.97 La 0.02 )(Hf x Sn 0.9-x Ti 0.1 )O3, where 0.85≤x≤0.9, exhibits excellent energy storage performance at high temperatures, can work stably and has high energy density and energy storage efficiency, and is suitable for high-temperature pulse capacitors. In addition, the material also has a lower phase transition electric field and can store and release energy at a lower voltage, thereby reducing the requirements for insulation technology, reducing system costs, and improving overall safety.

[0100] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A lead hafniumate-based antiferroelectric ceramic having a low phase transition electric field at high temperature, characterized in that: The chemical composition of the lead hafnium oxide-based antiferroelectric ceramic is (Pb 0.97 La 0.02 )(Hf x Sn 0.9-x Ti 0.1 )O3, where 0.85≤x≤0.

9.

2. The lead hafnate-based antiferroelectric ceramic with a low phase transition electric field at high temperature according to claim 1, characterized in that: The chemical composition of the lead hafnium oxide-based antiferroelectric ceramic is (Pb 0.97 La 0.02 )(Hf 0.85 Sn 0.05 Ti 0.1 )O3, x=0.

85.

3. The lead hafnate-based antiferroelectric ceramic with low phase transition electric field at high temperature according to claim 1, characterized in that: The lead hafniumate-based antiferroelectric ceramic exhibits antiferroelectric properties and has a double hysteresis loop under the test conditions of 100-120° C. and 10 Hz and an applied electric field of 10-40 kV / mm.

4. The lead hafnate-based antiferroelectric ceramic with a low phase transition electric field at high temperature according to claim 1, characterized in that: The lead hafnate-based antiferroelectric ceramic has a low phase transition electric field of 3.2 to 3.8 kV / mm under the test conditions of 100 to 120° C. and 10 Hz and an applied electric field of 10 to 40 kV / mm, and exhibits a low phase transition electric field of 3.0 to 3.4 J / cm 3 The releasable energy density, residual polarization intensity P r 0.08~0.3μC / cm 2 , the maximum saturation polarization intensity P m 50.2~52.7μC / cm 2 .

5. A method for preparing a lead hafnate-based antiferroelectric ceramic having a low phase transition electric field at high temperature according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, press (Pb 0.97 La 0.02 )(Hf 0.85 Sn 0.05 Ti 0.1 )O3, weighing PbO, La2O3, HfO2, SnO2 and TiO2 as raw materials, and sequentially performing a first ball milling, a pre-sintering and a second ball milling treatment to prepare a lead hafnium oxide-based antiferroelectric ceramic powder; S2, mixing the lead hafnium oxide-based antiferroelectric ceramic powder prepared in step S1 with a solvent, a dispersant, a binder and a plasticizer to obtain a lead hafnium oxide-based antiferroelectric ceramic slurry; S3, performing tape casting treatment on the lead hafnium oxide-based antiferroelectric current casting slurry obtained in step S2 to obtain a lead hafnium oxide-based antiferroelectric thick film; S4, hot pressing and isostatic pressing the lead hafnium oxide-based antiferroelectric thick film obtained in step S3 to obtain a ceramic green body; S5, performing debinding and sintering treatments on the ceramic green body obtained in step S4 to prepare a lead hafnium oxide-based antiferroelectric ceramic material.

6. The method for preparing the lead hafniumate-based antiferroelectric ceramic with low phase transition electric field at high temperature according to claim 5, characterized in that: In step S1, the dispersant for the primary ball milling and the secondary ball milling includes water or anhydrous ethanol, the medium used for ball milling is zirconia ball, the ball milling time is 12 to 18 hours, and the ball milling speed is 360 to 450 rpm; the pre-sintering temperature is 880 to 910°C, the pre-sintering insulation time is 2 to 3 hours, and the heating rate is 2 to 3°C / min.

7. The method for preparing the lead hafniumate-based antiferroelectric ceramic with low phase transition electric field at high temperature according to claim 5, characterized in that: In step S2, the solvent includes a mixture of anhydrous ethanol and butanone; the dispersant includes tributyl phosphate; the binder includes polyvinyl butyral; and the plasticizer includes a mixture of polyethylene glycol and benzyl-n-butyl-phthalate.

8. The method for preparing lead hafniumate-based antiferroelectric ceramics with low phase transition electric field at high temperature according to claim 5, characterized in that: In step S4, the hot pressing temperature is 45-60°C, the pressure is 120-150 MPa, and the hot pressing time is 8-10 min; the isostatic pressing temperature is room temperature, the pressure is 180-200 MPa, and the holding time is 10-15 min.

9. The method for preparing the lead hafniumate-based antiferroelectric ceramic with low phase transition electric field at high temperature according to claim 5, characterized in that: In step S5, the debinding process includes heating the temperature to 550-600°C at a heating rate of 0.5-1°C / min and keeping the temperature for 10-15 hours; the sintering process includes heating the temperature to 1250-1300°C at a heating rate of 1-2°C / min and keeping the temperature for 2-3 hours.

10. Use of the lead hafnate-based antiferroelectric ceramic with low phase transition electric field at high temperature according to any one of claims 1 to 4 in the field of pulse power and high-temperature energy storage.